A Philosophical Dictionary, Volume 06 - Voltaire, 1694-1778; Leigh, Oliver Herbrand Gordon; Morley, John, 1838-1923; Smollett, T. (Tobias), 1721-1771; Fleming, William F. (Salt Lake City, UT : Project Gutenberg, 2011)
"A Philosophical Dictionary, Volume 06" by Voltaire is an encyclopedic dictionary published in 1764. This alphabetically arranged work emerged from a dinner party challenge at Frederick II's Prussian court in 1752. Voltaire critiques religious institutions and champions tolerance, deism, and press freedom through compact, accessible articles. Designed to fit in one's pocket, this revolutionary text educated and provoked readers across Enlightenment Europe. While the public eagerly consumed multiple editions, religious authorities condemned it, burning copies in town squares across France and Switzerland. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Dictionnaire_philosophique
Release date is 2011-03-28
Produced by Andrea Ball, Christine Bell & Marc D'Hooghe (From images generously made available by the Internet Archive.)
Keywords: Philosophy -- Dictionaries; Criticism (Philosophy)